Ekstraksi Minyak Atsiri Pandan Wangi (Pandanus amaryllifolius Roxb.) dengan Lama Waktu Penyulingan yang Berbeda - Maya Damayanti; Sarifah Nurjanah; Anas Bunyamin; Totok Pujianto (Jurnal Ilmu Pertanian Indonesia, 2020)
The leaves of pandan wangi (Pandanus amaryllifolius Roxb.) are known as food flavor and can be extracted to produce essential oil. Extraction of its essential oil is usually conducted by distillation method that would give added value for this plant. This study aimed to study the effect of different durations of distillation process on the essential oils yield and quality of pandanus using water and steam distillation method. The method used in this research was experimental method with descriptive analysis. This research used five variants duration of distillation, which was repeated two times. The duration of distillation consisted of 2 hours, 4 hours, 6 hours, 8 hours, and 10 hours. The parameters observed to determine the best treatment consisted of the amount of yield produced and the quality parameters including specific gravity, refractive index, acid number, solubility in ethanol 90%, and ester number. Based on the results of the research conducted, distillation to produce the best yield is the duration of 8 hours with a yield value of 0.55%, while distillation to produce the best quality is the duration of 6 hours with a specific gravity of 1.0563 g/mL, refractive index 1.3473, the acid number was 3.274 mg KOH/g, solubility in ethanol 90% (1:1), and ester number of 96.06 mL HCl/g. Keywords: essential oil, pandan wangi, water and steam distillation